Association between thyroid hormone sensitivity and carotid plaque risk: a health examination cohort-based study - Gong, Rui; Wang, Shi; Ding, Hongqiong; Yu, Lixia; Xu, Ming; Xu, Sanping; Ling, Yan (Frontiers in Endocrinology, 2024)
Introduction: The involvement of thyroid hormone in cardiovascular disease remains debated. The aim of our research was to ascertain whether thyroid hormone sensitivity indices are related to carotid plaque (CAP) risk in the general population. Methods: We recruited 5,360 participants for health examinations to explore the correlation between thyroid hormone sensitivity indices and CAP risk. We then compared baseline characteristics of participants with CAP to those without CAP based on multivariate logistic regression analysis. Additionally, we conducted subgroup analyses stratified by gender and age to further elucidate this relationship. Results: Among the 5,360 participants, 1,055 (19.7%) were diagnosed with CAP. After adjusting for various confounding factors, our results showed a positive association between CAP risk and the indices (TFQI, PTFQI, TSHI, and TT4RI). Conversely, the FT3/FT4 ratio showed a negative correlation with CAP risk. Sex-based subgroup analysis revealed a stronger correlation between thyroid hormone sensitivity and CAP in females compared to males. In the age subgroup, the significant association was observed in older individuals (age >60) compared to middle-aged participants (age ≤60). Conclusion: Our study suggests a significant correlation between thyroid hormone sensitivity and CAP, particularly in females and participants over the age of 60.